A Role for Mucolytics and Expectorants in Aiding Inhaled Therapies in Asthma? [Response To Letter] - Kurukulaaratchy RJ; Rupani H; Fong WCG; Kyyaly A (Dove Medical Press, 2021)
Ramesh J Kurukulaaratchy,1–4 Hitasha Rupani,1 Wei Chern Gavin Fong,2,3 Aref Kyyaly2,3 1Department of Respiratory Medicine, University Hospitals Southampton NHS Foundation Trust, Southampton, UK; 2Clinical and Experimental Sciences, University of Southampton, Southampton, UK; 3David Hide Asthma and Allergy Research Centre, Isle of Wight NHS Trust, Isle of Wight, UK; 4NIHR Biomedical Research Centre, University Hospitals Southampton NHS Foundation Trust, Southampton, UKCorrespondence: Ramesh J KurukulaaratchyWei Chern Gavin Fong Clinical and Experimental Sciences, University of Southampton, Southampton, UKTel +44 238120 5232Email R.J.Kurukulaaratchy@soton.ac.uk; W.C.Fong@soton.ac.uk View the original paper by Dr Rupani and colleagues This is in response to the Letter to the Editor